Uso de fórceps na assistência ao parto vaginal: análise do uso durante a residência médica e na prática obstétrica pessoal - Kehdi, João Francisco Farhat (2024)
The use of forceps corresponds to a highly effective technical alternative when well indicated, however, we observed a progressive reduction in their use, thus, in Latin American countries there are no rates higher than 1.0% of births in which forceps are used. There are several reasons described for the small number of births assisted with forceps, despite these reasons, Specialty Societies agree that this clinical practice has a role in assisting vaginal births, recognizing the role of forceps in good obstetric practice in assisted births. There are some obstetrics teaching institutions that traditionally encourage the use of forceps, while in others this technique has not survived. We were interested in knowing how, in practice, graduates from different medical residency schools behave throughout their professional lives in obstetrics. This was an observational, cross-sectional and descriptive study, on specific knowledge regarding the indications and how to use obstetric forceps, as well as the frequency of its practice. We used questionnaires sent virtually, with the Google Forms® app, to medical residents in gynecology and to already trained specialists. We had the participation of 305 doctors, 45 of whom are still in medical residency, 61 graduated less than 5 years ago and 196 have been gynecologists for more than 5 years. The vast majority consider forceps training important, however less than half of them used forceps in the last year. In the results we compare different variables between those who use forceps and those who do not